Major Crop Combination and Diversification Regions in Kashmir Valley - Javaid Ahmad Andrabi (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Agriculture is the main source of revenue in Kashmir Valley as the bulk of population survives or bout 70% of the population survives on it. The Valley is geographically divided in to three zones like flood plains, Kerewas and Mountains. Variations in altitude, soil and climate has closely influenced the agricultural practices among various districts of Kashmir valley. In the present paper an attempt has been made to study crop combination region, cropping pattern and crop diversification in Kashmir valley.